Home Range Size, Density Estimation And Food Of Malayan Tapirs (Tapirus Indicus) At Krau Wildlife Reserve - Gani, Siti Khadijah Abd (2010)

(untitled)
This study was conducted in Krau Wildlife Reserve from November 2002 to May 2007 using camera-trapping, radio telemetry, direct observation and line transect techniques. It took over 698 trap-nights to accumulate 295 photographic captures of Malayan tapirs or 21 identified individuals, which constituted 73.37% of the total wildlife photos. An estimated density of Malayan tapirs is 7 individuals/100km2 with the estimated population size between 28 to 32 individuals. It is clearly showed that 100.00% of the photographs are recorded in between 2000 until 0600. None of the photograph is recorded in the day (0700 until 1900). Malayan tapirs were recorded significantly more often at Bayek Saltlick than other areas (p<0.05, t-test).